2021
DOI: 10.3390/antibiotics10020197
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Methicillin-Resistant Staphylococcus aureus from Community- and Hospital-Associated Infections: A Tertiary Care Center Study

Abstract: The community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has become increasingly prevalent in both community and hospital settings. The aim of this study was to determine the prevalence, molecular characteristics and antibiotic resistance profiles of CA-MRSA from community- and hospital-associated infections in a tertiary care hospital in Mangalore, India. Of 520 S. aureus isolates, 362 were from inpatients (IP) and 158 were from outpatients (OP). One-hundred and thirty-two MRSA isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
4
20
1
Order By: Relevance
“…Like our findings, CA-MRSA isolates containing the SCCmec type IV demonstrated stronger antibiotic resistance than HA-MRSA according to Preeja et al, 26 and CA-MRSA isolates were shown to be resistant to three or more antibiotic classes. MDR CA-MRSA has been reported worldwide as mentioned by Earls et al, 29 and Lee et al 30 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Like our findings, CA-MRSA isolates containing the SCCmec type IV demonstrated stronger antibiotic resistance than HA-MRSA according to Preeja et al, 26 and CA-MRSA isolates were shown to be resistant to three or more antibiotic classes. MDR CA-MRSA has been reported worldwide as mentioned by Earls et al, 29 and Lee et al 30 .…”
Section: Discussionsupporting
confidence: 87%
“…Higher prevalence reported by Buenaventura-Alcazaren et al 6 who observed that the prevalence of positive PVL-SCCmec IV community acquired MRSA isolates from HCWs was 33%. However, lower prevalence documented by Preeja et al, 26 who found that 12.3% of MRSA isolates were PVL-SCCmec IV community acquired MRSA.…”
Section: Discussionmentioning
confidence: 85%
“…The in-silico SCCmec typing revealed that strains P10 and R46 ST113 harbor SCCmec type IV, and therefore possibly CA-MRSA as SCCmec types IV and V are predominantly associated with CA-MRSA [12][13][14]. CA-MRSA are generally susceptible to non-β-lactam antibiotics and possesses the virulence-associated gene Panton-Valentine Leucocidin (PVL), whereas HA-MRSA are associated with nosocomial infections and are generally resistant to non-β-lactam antibiotics and do not possess the PVL gene [25]. The strain P10 contains a plasmid pI5S5 (HE579068.1), an unnamed plasmid "unnamed1" (CP030577.1), and three complete phages of length 42 kbp, 48.4 kbp, and 74.2 kbp.…”
Section: Discussionmentioning
confidence: 99%
“…As showed in the table-5, MRSA presented with highly resistant (Erythromycin-69.0) to lowest resistant (Linozolid-7.8). Another research also found that 44.4 percent of MRSA isolates were resistant to cefotaxime, 40.7% to gentamicin, 86.4% to ciprofloxacin, 40.7 percent to clindamycin, 66.7% to erythromycin, and 49.4% to ofloxacin [32].…”
Section: Discussionmentioning
confidence: 91%